2018
DOI: 10.1038/s41388-018-0421-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor penetrating peptides inhibiting MYC as a potent targeted therapeutic strategy for triple-negative breast cancers

Abstract: Overexpression of MYC oncogene is highly prevalent in many malignancies such as aggressive triple-negative breast cancers (TNBCs) and it is associated with very poor outcome. Despite decades of research, attempts to effectively inhibit MYC, particularly with small molecules, still remain challenging due to the featureless nature of its protein structure. Herein, we describe the engineering of the dominant-negative MYC peptide (OmoMYC) linked to a functional penetrating 'Phylomer' peptide (FPPa) as a therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 70 publications
(81 reference statements)
3
50
0
Order By: Relevance
“…Similarly to what has been shown for Omomyc alone, FPPa-Omomyc blocked proliferation, induced apoptosis [85,86], disrupted MYC/MAX interaction, downregulated MYC-activated gene sets and de-repressed MYC-repressed ones. FPPa-Omomyc showed in vivo efficacy in a subcutaneous patient-derived mouse model of triple negative breast cancer (TNBC) when administered locally, decreasing proliferation, causing apoptosis, downregulating PD-L1, and extending mouse survival [85]. In this report, Omomyc alone did not induce those changes but was used at a much lower dose than in our studies in NSCLC models.…”
Section: Ongoing Research and Future Directionssupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly to what has been shown for Omomyc alone, FPPa-Omomyc blocked proliferation, induced apoptosis [85,86], disrupted MYC/MAX interaction, downregulated MYC-activated gene sets and de-repressed MYC-repressed ones. FPPa-Omomyc showed in vivo efficacy in a subcutaneous patient-derived mouse model of triple negative breast cancer (TNBC) when administered locally, decreasing proliferation, causing apoptosis, downregulating PD-L1, and extending mouse survival [85]. In this report, Omomyc alone did not induce those changes but was used at a much lower dose than in our studies in NSCLC models.…”
Section: Ongoing Research and Future Directionssupporting
confidence: 69%
“…PYC Therapeutics (formerly Phylogica), linked Omomyc to a functional penetrating "Phylomer" peptide (FPPa) and tested the efficacy of this new entity against plasmacytoma, leukemia and breast cancer cells in vitro [86]. Similarly to what has been shown for Omomyc alone, FPPa-Omomyc blocked proliferation, induced apoptosis [85,86], disrupted MYC/MAX interaction, downregulated MYC-activated gene sets and de-repressed MYC-repressed ones. FPPa-Omomyc showed in vivo efficacy in a subcutaneous patient-derived mouse model of triple negative breast cancer (TNBC) when administered locally, decreasing proliferation, causing apoptosis, downregulating PD-L1, and extending mouse survival [85].…”
Section: Ongoing Research and Future Directionsmentioning
confidence: 99%
“…The benefit of inhibiting Myc has been demonstrated by multiple studies, [19] which indicated that interfering with Myc function does not only lead to cell growth arrest, but also to energetic crisis, anti-tumor immune reprogramming, and cancer cell death. The potential use of Omomyc as a therapeutic mini-protein has only emerged recently [40,41] and, to date, this is the first and only report of its application in the IB format, which establishes the feasibility of its topical administration by intratumoral injection directly to the tumor site. The potential use of Omomyc as a therapeutic mini-protein has only emerged recently [40,41] and, to date, this is the first and only report of its application in the IB format, which establishes the feasibility of its topical administration by intratumoral injection directly to the tumor site.…”
Section: Resultsmentioning
confidence: 80%
“…We have shown that OmoMYC is able to inhibit the growth of breast carcinoma cells when injected orthotopically in TNBC animal models having intact immune systems [26]. In addition to potent tumor inhibition and induction of Caspase-3 apoptosis, OmoMYC induced a suppression of the immune checkpoint protein PD-L1.…”
Section: Myc (Myc Proto-oncogene Bhlh Tf)mentioning
confidence: 95%
“…In addition to potent tumor inhibition and induction of Caspase-3 apoptosis, OmoMYC induced a suppression of the immune checkpoint protein PD-L1. Moreover, we found that penetrability of the OmoMYC peptide was a limiting factor for its therapeutic activity in these cancers [26]. To overcome this, we engineered the OmoMYC sequence with state-of-the-art cell penetrating sequences selected from large peptide libraries (Phylomers).…”
Section: Myc (Myc Proto-oncogene Bhlh Tf)mentioning
confidence: 99%